Novelty detection of foreign objects in food using multi-modal X-ray imaging - Einarsdottir, Hildur; Emerson, Monica Jane; Clemmensen, Line Harder; Scherer, Kai; Willer, Konstantin; Bech, Martin; Larsen, Rasmus; Ersboll, Bjarne Kjaer; Pfeiffer, Franz (Food Control, 2016)
In this paper we demonstrate a method for novelty detection of foreign objects in food products using grating-based multimodal X-ray imaging. With this imaging technique three modalities are available with pixel correspondence, enhancing organic materials such as wood chips, insects and soft plastics not detectable by conventional X-ray absorption radiography. We conduct experiments, where several food products are imaged with common foreign objects typically found in the food processing industry. To evaluate the benefit from using this multi-contrast X-ray technique over conventional X-ray absorption imaging, a novelty detection scheme based on well known image- and statistical analysis techniques is proposed. The results show that the presented method gives superior recognition results and highlights the advantage of grating-based imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dark-field imaging; Foreign object detection; Novelty detection; Phase-contrast imaging; Texture analysis; X-ray radiography